Growth and the cancer caregiving experience: psychometric properties of the Portuguese posttraumatic growth inventory - Teixeira, Ricardo João (2013)
The purpose of the present study was to investigate the psychometric properties of the Portuguese version of the Posttraumatic Growth Inventory (PTGI) and relate posttraumatic growth with psychological morbidity. This is a cross-sectional study with a sample of 214 adult children of cancer patients. Additionally, a comparison group was recruited with 78 participants without a chronically ill parent. Measures of distress, posttraumatic stress disorder (PTSD) symptoms, and posttraumatic growth were collected. The original five-factor structure of the PTGI was maintained, with satisfactory internal consistency. The reorganization of the items in five factors was similar to the solution found in the original PTGI study, except for four items. Positive correlations between posttraumatic growth and PTSD symptoms/distress were significant. Women showed significantly higher posttraumatic growth. Adult children with parental cancer, and with probable PTSD, showed higher scores on the PTGI. Regression analysis revealed that PTSD symptoms were associated with higher posttraumatic growth, after controlling for demographic and clinical variables. Analysis with the comparison group showed that differences in posttraumatic growth were observed as a function of a shattered experience. This study confirmed the multidimensionality of the posttraumatic growth construct, underscoring the importance of considering the subjective nature of the shattered event, and the experience of emotional distress with parental cancer.